PENGARUH BUDAYA ORGANISASI, STRES KERJA DAN KOMITMEN TERHADAP KINERJA KARYAWAN CV. BINTANG KARYA PUTRA DI SURABAYA - H. Edy Sutrisno (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
CV. Bintang Karya Putra in Surabaya is one of a  private company in construction area and cleaning service. In facing emulation is required by pre-eminent human resource and professional, therefore hardly is required quality of human resource, causing can reach optimal performance executed by all company employee. Employee performance hardly influenced by organization culture, stress job and commitment of employee. This research aim to know are there influence between organization cultures, stres job and commitment to employee performance. Sample taken is 75 employees of CV. Bintang Karya Putra in Surabaya. Based on result of knowable finding:Based on result of  the research earns to know that there are significant influence between organization culture to employee performance of  CV. Bintang Karya Putra.Based on result of  research earns to know that there are significant influence between job stres  to employee performance of CV. Bintang Karya Putra.Based on result of the research earns to know that there are significant influence between commitment to employee performance of CV. Bintang Karya Putra.Variable that is very dominant influential to employee performance of CV. Bintang Karya Putra is variable organization culture.Contribution given by organization culture, stress job and commitment to employee performance of CV. Bintang Karya Putra is 83,50 %. While the rest 16,50 % is variables that is not predicted in this research